R&D, Competition and Growth with Human Capital Accumulation Revisited - Dominique Bianco (Swiss Journal of Economics and Statistics, 2012)
In this paper, we have presented a generalization of Bucci's (2003) model in which have disentangled the monopolistic mark-up in the intermediate goods sector, the intermediate goods share in the final output and the returns to specialization in order to have a better measurement of competition. Indeed, unlike Bucci (2003), in our model, the measure of competition is completely independent of the intermediate goods share in the final output and the returns to specialization. Our main finding is that, unlike Bucci (2003), we show that the competition does not play any role in growth. This result is explained by the complementarity of innovation and human capital assumed in the research production. Moreover, we have shown that an increase in competition raises the level of production per capita, increasing consumer's welfare.
Keywords: D43; J24; L16; O31; O41; 330; Endogenous growth; horizontal differentiation; technological change; imperfect competition; human capital